2020
DOI: 10.1016/j.pec.2020.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Giving and receiving a diagnosis of a progressive neurological condition: A scoping review of doctors’ and patients’ perspectives

Abstract: Objective: Delivering a life changing diagnosis can be a distressing experience for patients and a challenging task for professionals. Diagnosis delivery can be especially difficult for individuals with neurodegenerative diseases such as motor neurone disease (MND), multiple sclerosis (MS) and Parkinson's disease (PD). This review aims to scope the literature on doctors' and patients' perspectives on diagnosis delivery for these conditions in order to enhance our understanding in this area and identify potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 80 publications
3
45
1
Order By: Relevance
“…Despite the emotional toll of breaking bad news, dealing with patients' emotional reactions did not seem to present a particular challenge for the participants of this survey. However, studies of patients with MNDDs have shown that patients are often dissatisfied with the lack of empathy shown by doctors during diagnosis delivery [10]. The seemingly contradictory finding here in that participants in this survey reported strong competency in this domain could either be attributed to participation bias (see limitations below) or different views and expectations between patients and professionals regarding the emotional aspects of the consultation.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Despite the emotional toll of breaking bad news, dealing with patients' emotional reactions did not seem to present a particular challenge for the participants of this survey. However, studies of patients with MNDDs have shown that patients are often dissatisfied with the lack of empathy shown by doctors during diagnosis delivery [10]. The seemingly contradictory finding here in that participants in this survey reported strong competency in this domain could either be attributed to participation bias (see limitations below) or different views and expectations between patients and professionals regarding the emotional aspects of the consultation.…”
Section: Discussioncontrasting
confidence: 56%
“…In particular, several chronic neurological conditions, such as Parkinson's disease (PD), multiple sclerosis (MS) and Huntington's disease (HD), are incurable, have a progressive nature and impact both physical and cognitive functions [8], while others, such as motor neurone disease (MND), can also be more immediately life threatening [9]. A scoping review of doctors' and patients' perspectives on giving and receiving the diagnosis of MND, MS or PD [10] revealed mixed results regarding patients' experiences and satisfaction with how diagnosis delivery was handled. The main factors which contributed to negative patient experiences were the often-limited duration of the consultation, inadequate information provision and a perceived insensitive approach by the professional breaking the news.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the importance of psychological approaches in people with PD has received more recognition compared to other neurodegenerative conditions, such as Huntington’s disease and motor neuron disease (Anestis, Eccles, Fletcher, French, & Simpson, 2020; Simpson et al, 2019; Zarotti, Dale, Eccles, & Simpson, 2020; Zarotti, Mayberry, Ovaska‐stafford, Eccles, & Simpson, 2020), the current literature around psychological interventions for PD is mainly characterized by low‐level and/or underpowered studies, and more comprehensive high‐powered RCTs are urgently needed. In addition, since only five studies out of 56 involved samples with a mean age lower than 60, all of which showed promising results (Berardelli, Pasquini, Bloise, et al, 2015; Dreisig et al, 1999; Lundervold et al, 2013; Okai et al, 2013; Sproesser et al, 2010), further investigations are required to explore the impact of psychological interventions in younger patients, in particular due to the potentially lower severity of cognitive and motor difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review evaluated the time of diagnosis in adults with rare and neurodegenerative diseases, but without genetic transmissibility, such as Amyotrophic Lateral Sclerosis (ALS), Multiple Sclerosis and Parkinson's Disease in European countries, Australia and the United States. Despite an increase in satisfaction regarding the transmission of the diagnosis in more recent articles, there was frequent dissatisfaction with the quality and nature of the information, with the lack of emotional support, content predominantly focused on technique and less on being, in addition to insu cient time to greater doctor-patient interaction at the time of diagnosis (23). Eenennaam et al (2020) developed a guide for communicating prognosis for ALS patients through a systematic review and consensus evaluated by neurologists, rehabilitating doctors, health researchers, patients, family members, an ethics specialist and spiritual counselors (24).…”
Section: Discussionmentioning
confidence: 99%